2022
DOI: 10.1021/acsomega.2c01705
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cytochrome P450s with Key Roles in Determining Herbicide Selectivity in Maize

Abstract: Safeners such as metcamifen and benoxacor are widely used in maize to enhance the selectivity of herbicides through the induction of key detoxifying enzymes, notably cytochrome P450 monooxygenases (CYPs). Using a combination of transcriptomics, proteomics, and functional assays, the safener-inducible CYPs responsible for herbicide metabolism in this globally important crop have been identified. A total of 18 CYPs belonging to clans 71, 72, 74, and 86 were safener-induced, with the respective enzymes expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…Our data suggest that no changes in tembotrione absorption or translocation that could confer resistance in KCTR (Figure 2). Triketone herbicides are widely used for weed control in corn as it can rapidly metabolize this herbicide into more polar and less toxic metabolites because of Phase I hydroxylation and dealkylation mediated by CYP activity (Brazier-hicks et al, 2022). In this research, the metabolic profiles of tembotrione showed presence of metabolites M1 and M3 in corn (Figures 3G, H), whereas in Palmer amaranth, M1 and M2 were identified as major metabolites at 6 HAT (Figures 3A, 3C).…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Our data suggest that no changes in tembotrione absorption or translocation that could confer resistance in KCTR (Figure 2). Triketone herbicides are widely used for weed control in corn as it can rapidly metabolize this herbicide into more polar and less toxic metabolites because of Phase I hydroxylation and dealkylation mediated by CYP activity (Brazier-hicks et al, 2022). In this research, the metabolic profiles of tembotrione showed presence of metabolites M1 and M3 in corn (Figures 3G, H), whereas in Palmer amaranth, M1 and M2 were identified as major metabolites at 6 HAT (Figures 3A, 3C).…”
Section: Discussionmentioning
confidence: 55%
“…Nsf1/Ben1 (gene named for nicosulfuron, Nsf, and bentazon, Ben) identified as the single major locus in corn which corresponded to CYP81A9 was implicated in resistance to nicosulfuron, a sulfonylurea herbicide (Williams and Pataky, 2008;Choe and Williams, 2020). Hitherto, few herbicides metabolizing CYPs have been expressed in heterologous system and characterized in plants (Dimaano et al, 2020;Brazier-hicks et al, 2022). CYP81A9 of corn that was found to metabolize multiple herbicides, including mesotrione, tembotrione and sulcotrione through the oxidation of cyclohexanedione ring (Brazier-hicks et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although CYP72A27 is a cytochrome p450, its identification here is somewhat unexpected, as it belongs to the CYP clan 72 group of cytochrome p450s. Members of this clan are generally associated with secondary metabolism, while clan 71 enzymes, such as CYP81A9 , are responsible for herbicide detoxification (Prall et al 2016; Brazier-Hicks et al 2022). However, sulfonylurea herbicide metabolism via clan 72 enzymes has been shown in other crops, such as CYP72A31 in Oryza indica (Saika et al 2014) and CYP749A16 in Gossypium hirsutum (Thyssen et al 2018).…”
Section: Discussionmentioning
confidence: 99%